Increasing Primary School Pupil’s Interest, Self-Concepts and Achievement in Trigonometry and Geometry Using Peer Teaching Approach - Yukwa, Bernard A.; Paul, Caleb; Yusuf, Kemuel K. (International Journal of Humanities, Education, and Social Sciences, 2024)
This study focuses on the effect of peer teaching approach on primary schools pupils’ interest, self-concept and academic achievement of geometry and trigonometry. The objectives of the study were to: determine the level of interest by Primary School Pupils in learning geometry and trigonometry when peer teaching approach is used as instructional strategy, Find out the level of self-concept pose by primary school pupils exposed to peer teaching approach and Determine the Academic Achievement of Primary school pupils who are exposed to peer teaching approach. The study adopted quasi-experimental design. Sample of 50 pupils were used for data collection. Results of the study revealed that there is a significant difference on pupils’ interest, self-concept and academic achievement when exposed to peer teaching approach. As all the three hypotheses were accepted at 5% level of significance. It was recommended that teachers should incorporate group learning among pupils in other to build their competency.